Inclusão de farelo de arroz integral em rações para leitões na fase inicial - Gomes, Thalles Ribeiro (2010)
Two experiments were led, with the objective of evaluating the effects of the inclusion of whole rice meal (WRM) in rations for piglets in the day care phase. In the 1st experiment, they were appraised the performance, the diarrhea incidence, as well as the economical viability. Were used 60 piglets, female and male castrated, of the 21 to the 42 days of age, with initial weight of 5.4 ± 1.44 kg. The experimental design was completely randomized design with five levels of inclusion of WRM (0.0, 5.0, 10.0, 15.0 and 20.0%) and six replicates per treatment, and the experimental unit (parcel) it was incorporated by two animals. The results showed that the daily mean feed intake (DMFI), daily mean weight gain (DMWG), the feed conversion (FC) and diarrhea incidence did not differ significantly (P> 0.05) for the different levels of inclusion of WRM. The economic analysis shows the viability the inclusion of until 20.0% of WRM. In the 2nd experiment they were appraised the feeding forms on the performance, as well as the economical viability. Were used 64 piglets, female and male castrated, of the 43 to the 67 days of age, with initial weight of 10.73 ± 1.85 kg. The experimental design was completely randomized in a factorial 4 x 2, four levels of inclusion of WRM (0.0, 10.0, 20.0 and 30.0%) and two feeding forms (ration dry and wet ration), with four replicates per treatment, the experimental unit consisted of two animals (parcel). The results showed that the daily mean feed intake (DMFI), daily mean weight gain (DMWG) and the feed conversion (FC) did not differ significantly (P> 0.05) for the different levels of inclusion of WRM. The economic analysis showed that the inclusion of 30.0% of WRM showed the best economic answer. It was ended that the supply of whole rice meal is viable until the level of 20.0% in the diets of pigs in the period initial I and until the level of 30.0% in the initial period II of the day care phase, independent in the feeding forms.